PENDIDIKAN KESEHATAN DALAM CUCI TANGAN LANGKAH SEDERHANA UNTUK CEGAH PENYAKIT DI SMK ISTIQOMAH MUHAMADIYAH 4 SAMARINDA - Bachtiar Safrudin; Ayu Putri S; Citra Maulidya; Daysila Sri M; Dhea Lilia Putri P; Erika Syavira; Gita Anisa M; M Raihan G; Najla Dalilah R Z; Nia Fauziah; Shinta Dwie Lestari; Suwaldi Pradana; Tankeke; M Kemal A (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Health education on the importance of proper handwashing was conducted as part of efforts to prevent infectious diseases in the school environment. Handwashing is a clean and healthy lifestyle behavior (PHBS) that is very simple to perform yet has a significant impact on reducing the incidence of diseases, particularly diarrhea, acute respiratory infections (ARI), influenza, and skin infections. These diseases are generally caused by viruses, bacteria, and germs that are often transmitted through dirty hands. Therefore, education on correct handwashing techniques needs to be provided early to students, considering that schools are high-activity environments with intense interaction among individuals. This outreach activity aims to increase students' knowledge about the benefits of handwashing, the appropriate times to wash hands, and the practice of the six-step handwashing method according to WHO standards. In addition to enhancing knowledge, this activity also aims to build daily habits so that students can independently, consistently, and correctly apply handwashing. This activity was carried out at SMK Istiqomah Muhammadiyah 4 Samarinda with 22 respondents. The outreach was conducted through several stages: a pre-test, an interactive lecture, a direct handwashing demonstration, hands-on practice by students, and a post-test as the final evaluation. The media used in this activity included PowerPoint presentations, leaflets, and posters illustrating handwashing steps. The lecture method was chosen to provide a fundamental understanding of what handwashing is and why it is important. Furthermore, the demonstration aimed to clearly show the six-step handwashing technique, covering rubbing the palms, back of the hands, between fingers, back of fingers, thumbs, and fingertips. This stage greatly helped students understand the difference between ordinary handwashing and correct, effective handwashing. The results of the activity showed that students' knowledge increased significantly after the outreach. Based on the pre-test results, some students only had